Vages Terrain Fragmente einer Standortwahl von übermorgen - Becker, Jerome; Grandel, Tobias Gunnar; Miessgang, Madlyn; Mitteregger, Mathias; Sattlegger, Sebastian (TU Wien Academic Press, 2023)
Where will we live? Where will we be when we work or relax? Who or what will decide about this? What possibilities will urban agglomerations offer for everyday spatial practice? What significance will local differences hold? How will we distribute ourselves on a damaged planet, and where will what be available to whom? This anthology is an invitation to abandon familiar ways of looking at things and to take a new look at what a choice of location in the city of the future might look like. Different actors were invited to explore seven concepts of apparent consistency in essays, interviews or artistic contributions: Freedom, Fear, Chaos, Tolerance, Prestige, Permanence and Fake. The book does not provide a linear narrative but invites the reader to cross-read and reread.